THE EFFECT OF LIVE BODY WEIGHT AT SLAUGHTER ON PERFORMANCE, CARCASS TRAITS AND BODY COMPOSITION OF AWASSI LAMBS - Yateem, CH. A. M.; Alkass, J.E.; Mustafa, K.N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
To examine the effect of different slaughter weights on performance, carcass traits and body composition, twenty five weaned Awassi lambs (19.00 ± 0.12 kg) were divided equally and randomly into five groups. All groups were fed individually ad lib on concentrated diet contained 15.1 % crude protein and 12.2, MJ/kg metabolizable energy. Lambs were slaughtered at five different live weights (20, 25, 30, 35 and 40 kg). Results revealed that daily gain in weight increased from its lowest value (115.7 g) at 20 kg, to (338.8 g) at 30 kg and there after declined to (299.9 g ) in lambs slaughtered at 49 kg. This was associated by a significant decline (P≤0.01) in feed conversion ratio. The daily dry mater intake was increased (P≤0.01) as the body weight increased. Dressing percentage, Rib eye area and back fat thickness increased (P≤0.01) with an increase of slaughter weight. While, the proportion of lean, bone and lean: fat ratio decreased (P≤0.01) from lighter to heavier weight. On the other hand, fat percentage and Lean: bone ratio increased (P≤0.01) as the slaughter weight increased